2022
DOI: 10.1093/cvr/cvac066.181
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin induces measurable vascular toxicity: assessment in a clinical and preclinical study

Abstract: Funding Acknowledgements Type of funding sources: Public Institution(s). Main funding source(s): Fund for Scientific Research (FWO) Flanders INSPIRE project (H2020-MSCA-ITN program) Background The chemotherapeutic doxorubicin (DOX) is frequently used to treat a wide variety of cancers, but the cardiotoxic side effects limits its clinical use in some patients. Additionally, DOX contributes to vascular toxicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
6
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 0 publications
4
6
1
Order By: Relevance
“…and organs were collected and weighed for further analysis. For proteomics, murine cardiac tissue from a historical study was used, previously reported in Bosman et al [12]. These mice underwent the same treatment protocol as the animals used in this study.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…and organs were collected and weighed for further analysis. For proteomics, murine cardiac tissue from a historical study was used, previously reported in Bosman et al [12]. These mice underwent the same treatment protocol as the animals used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…A detailed echocardiographic analysis of the DOX murine model has already been performed by Bosman et al, focusing on vascular and LV systolic function. We previously described EC dysfunction occurring early on in DOX-induced CTR-CVT [12]. The present study focuses on diastolic dysfunction and the identification of molecular changes in DOX-induced CTR-CVT in the aforementioned model.…”
Section: Evaluation Of Dox-induced Cardiotoxicity In Micementioning
confidence: 98%
See 3 more Smart Citations